Attracting, Motivating and Engaging Gen 'Y' an Infrastructure Organization (Global Business Management Review (GBMR), 2022)
Attracting, Motivating and Engaging employees have been remained key issues for any organization. Today the proportion of Generation Y (GenY) at workplace is increasing day by day. GenY will be the largest percentage of employed workforce for next 30 years in India. Attracting, motivating andengaging this workforce through robust talent identification, development and engagement plans will be the only way that organizations will reap the benefits of the dividend promised by Young India. This paper reviews recent literature for managing GenY effectively. It explored career aspirations and motivators for GenY employees in a large infrastructure organization. The primary data have been collected from GenY employees using questionnaire survey and focused group discussions about their career aspirations and motivators. The primary results shown that GenY in the organization prefers career which builds their technical & functional competence, provides managerial tasks and variety. Advancement and considerate & sympathetic supervisor are found as key motivators. The paper further discussed HR interventions to attract, motivate and engage the selected group of people.